A língua escrita em ciclo final de alfabetização: uma interface com consciência fonológica - Bernardelli, Anelise dos Santos (2015)
This paper presents the results of a survey that investigated student performance, in relation to skills related to different levels of phonological awareness, worked in an interactive way to reading and writing. The study was conducted with students of the literacy final cycle of João Pessoa. Through this research process, qualitative, descriptive and interventional, we promote the progress of these students in relation to skills related to phonological awareness and written language. The research, theoretically grounded in Capovilla and Capovilla (2010, 2011), Lemle (2009), Dehaene (2012) and Solé (2009), was developed in four stages: 1st) verification of reading acquisition stage and writing; 2nd) application of the pre-test to analyze student performance in relation to activities that combine phonological awareness, reading and writing; 3rd) development of didactic proposal prepared on the basis of pre-test results and 4th) application of the post-test to check the performance of students after intervention proposal. The material obtained in each of these steps is the corpus of the work. In the pre-test analysis, we identified various difficulties related to awareness of words, syllables, rhymes and alliterations and phonemes. Based on this analysis, we developed a didactic proposal from the Pacto Nacional pela Alfabetização na Idade Certa- PNAIC (BRASIL, 2013). After the development of the intervention, we verified, through the post-test analysis, students in different stages of written language acquisition advanced skills worked in relation to the pre-test. These results point to the importance of a work focused on the development of reading, writing and phonological awareness during the literacy process, particularly, in relation to students who are in the early stages of this process.